2006
DOI: 10.1253/circj.70.1064
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Blood Glucose in Patients With Cardiogenic Shock

Abstract: Background Although an elevated blood glucose has prognostic value in cardiovascular disease, few data are available regarding its prognostic value for patients across the spectrum of cardiogenic shock. Method and Results A total of 81 patients with cardiogenic shock whose blood glucose and adrenaline were measured on arrival at the emergency room (ER) were enrolled in this prospective study. The primary endpoint was death from any cause in hospital. The rate of death was 12.3% (10/81), and the glucose level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…It is well documented that glucose abnormalities are related to poor prognosis in patients with CAD. [25][26][27] Recent epidemiological, clinical and experimental data have suggested that controlling blood glucose in the non-fasting state, especially in the postprandial period, can reduce the risk of the macro-angiopathic complications of DM. [28][29][30] Monitoring of the HbA1c levels assists in reducing the risk of microvascular complications, 31 but unfortunately, low HbA1c levels are not sufficient to decrease the risk of macrovascular complications, especially the risk of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that glucose abnormalities are related to poor prognosis in patients with CAD. [25][26][27] Recent epidemiological, clinical and experimental data have suggested that controlling blood glucose in the non-fasting state, especially in the postprandial period, can reduce the risk of the macro-angiopathic complications of DM. [28][29][30] Monitoring of the HbA1c levels assists in reducing the risk of microvascular complications, 31 but unfortunately, low HbA1c levels are not sufficient to decrease the risk of macrovascular complications, especially the risk of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…For practical purpose, continuous variables were transformed into categorical variables, which were assessed by normal range or cutoff value as determined in previous studies. 11,12 The covariates considered clinically relevant or that showed a univariate relationship with outcome ( P ≤0.2) were entered into a multivariable regression model. Clinically intercorrelated variables were excluded from the model.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia at admission is one of the strongest predictors of short‐term mortality in patients with CS (Abdin et al, 2018; Kataja et al, 2017; Leor et al, 1993; Tada et al, 2006). Peak glycemia is an independent predictor of mortality in STEMI patients that develop CS, and survivors show lower glycemic variability than nonsurvivors (Lazzeri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%